Organizational uncertainty: a complex approach to decision making (Gestión y Gerencia, 2026)
This essay goes through the conceptual evolution of organizational uncertainty, starting from the classic vision, where it was intended to control uncertainty, until achieving ontological and complex reasoning, all achieved through documentary and bibliographic review, under a qualitative approach, to end by assuming that the BANI model (Fragile, Anxious, Non-linear and Incomprehensible) explains the current organizational environment, characterized by integrating the Theory of Complex Adaptive Systems (CAS), Organizational Leadership, Emotional Intelligence and Digital Transformation. Therefore, it is necessary for management to assume uncertainty as a characteristic of current organizations, which entails their transformation to an organization with Complex Adaptive Systems (Zapien, 2025), where technology drives fluidity and collaboration. Furthermore, it is concluded that leadership stimulated change and innovation within work teams (sensemaking), using emotional intelligence (Rodríguez et al., 2024). It ended with the conviction that it is necessary to combine advanced analytics and human sensitivity to achieve sustainability, with ethics and organizational governance as central axes.
Keywords: Organizational uncertainty; emotional intelligence; leadership; BANI model; complex adaptive systems